Computed Tomography–Based Measurements of the Cochlear Duct: Implications for Cochlear Implant Pitch Tuning. Issue 3 (May 2021) - Jiam, Nicole T.; Gilbert, Melanie; Mo, Jonathan; Jiradejvong, Patpong; Limb, Charles J.
Abstract : Objectives: To determine the sources of variability for cochlear duct length (CDL) measurements for the purposes of fine-tuning cochlear implants (CI) and to propose a set of standardized landmarks for computed tomography (CT) pitch mapping. Design: This was a retrospective cohort study involving 21 CI users at a tertiary referral center. The intervention involved flat-panel CT image acquisition and secondary reconstructions of CIs in vivo. The main outcome measures were CDL measurements, CI electrode localization measurements, and frequency calculations. Results: Direct CT-based measurements of CI and intracochlear landmarks are methodologically valid, with a percentage of error of 1.0% ± 0.9%. Round window (RW) position markers (anterior edge, center, or posterior edge) and bony canal wall localization markers (medial edge, duct center, or lateral edge) significantly impact CDL calculations [ F (2, 78) = 9.9, p < 0.001 and F (2, 78) = 1806, p < 0.001, respectively]. These pitch distortions could be as large as 11 semitones. When using predefined anatomical landmarks, there was still a difference between researchers [ F (2, 78) = 12.5; p < 0.001], but the average variability of electrode location was reduced to differences of 1.6 semitones (from 11 semitones. Conclusions: A lack of standardization regarding RW and bony canal wall landmarks results in great CDL measurement variability and distorted pitch map calculations. We propose using the posterior edge of the RW and lateral bony wall as standardized anatomical parameters for CDL calculations in CI users to improve pitch map calculations. More accurate and precise pitch maps may improve CI-associated pitch outcomes. Abstract : Supplemental Digital Content is available in the text.